Pengaruh Pengetahuan Tentang Bank, Tingkat Literasi Keuangan Syariah, Kualitas Pelayanan dan Kepercayaan Masyarakat Terhadap Minat Menabung di Bank Syariah - Raharjo, Dirham; Sriyono; Herlinda Maya Kumala Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the influence of knowledge about banks, level of sharia financial literacy, service quality and public trust on interest in saving at sharia banks. The sample used in this research consisted of 100 respondents. This type of research uses primary data obtained from web data books. Types of primary data with techniques using the purposive sampling method with the Slovin formula with data processing using SPSS Version 25 software. The data analysis techniques in this research are data quality tests, namely validity and reliability tests, while classical assumption tests include normality tests, heteroscedasticity tests, multicollinearity tests. Multiple linear regression analysis, and hypothesis testing, namely partial test (t test) and f test. The results of this research show that the influence of knowledge about banks (X1) on interest in saving (Y) is the variable knowledge about banks shows that the value of t calculated is 5.815 with a significance value of 0.043. The results show that t count > t table (5815 > 1.661) and significance (0.000 < 0.05). So it can be concluded that the variable Knowledge about Banks has a positive and significant effect on Interest in Saving. Influence of Islamic Financial Literacy (X2) on Interest in Saving (Y) Variable Islamic Financial Literacy Sharia shows that the value of t calculated is 2.290 with a significance value of 0.010. The results show that t count > t table (2.290 > 1.661) and significance (0.024 < 0.05). So it can be concluded that the Sharia Financial Literacy variable has a positive and significant effect on Interest in Saving. Influence of service quality (X3) on interest in saving (Y) Service quality variab shows that the value of t calculated is 2.454 with a significance value of 0.016. The results show that t count > t table (2.454 > 1.661) and significance (0.016 < 0.05). So it can be concluded that the variable service quality has a positive and significant effect on interest in saving. Influence of Public Trust (X4) towards Interest in Saving (Y) The Public Trust variable shows that the value of t calculated is 2.008 with a significance value of 0.000. The results show that t count > t table (2.008 > 1.661) and significance (0.047 < 0.05). So it can be concluded that the Public Trust variable has a positive and significant effect on Interest in Saving. Based on the results of the F test, the F value is 29.501 and the significance value is 0.000 (< 0.05). So it can be concluded that simultaneously Knowledge about Banks, Sharia Financial Literacy Level, Financial Quality, and Public Trust have a significant effect on Interest in Saving.